Elevated serum levels of proinflammatory cytokines potentially correlate with depression and anxiety in colorectal cancer patients in different stages of the antitumor therapy - Miranda, Diego O. (2018)
Depression and anxiety, the most important psychological disorders in cancer patients, have now been considered as psychoneuroimmunological disorders, in which peripheral immune activation, through the release of proinflammatory cytokines, is implicated in the variety of behavioral, neuroendocrine and neurochemical alterations associated with these disorders. Along with the tumor itself, cancer treatment can also contribute to exacerbate the production of proinflammatory cytokines. This study aimed to investigate whether proinflammatory cytokine levels are related to depression and anxiety in CRC patients in different stages of the antitumor therapy We evaluated 60 patients in three stages of antitumor therapy (Pre-chemotherapy, Under chemotherapy and Post-chemotherapy, n = 20 in each group) and 20 healthy volunteers by the Hospital Anxiety and Depression Scale (HADS). Serum levels of cytokines were measured by CBA. Depression and/or anxiety were found at clinically relevant levels in CRC patients during all antitumor therapy. Patients in pre-chemotherapy group exhibited the highest concentrations of pro-inflammatory cytokines and the lowest levels of IL-10. In latter stages of treatment, cytokines reached levels similar to the control group. Correlation analysis between HADS score and cytokine serum levels revealed positive associations of anxiety and/or depression with IL-1 beta, IL-6, IL-8, and TNF-alpha, and a negative correlation with IL-10, suggesting that cytokines are involved in the pathophysiology of these psychological disorders in CRC patients. A better understanding of the molecular mechanisms involved in these psychological disorders will allow the design of new therapeutic strategies to assist in alleviating such symptoms in cancer patients.